Życie i kariera Orybazjusza w świetle relacji źródłowych - Jagusiak, Krzysztof; Kokoszko, Maciej (Przegląd Nauk Historycznych, 2011)
The article makes an attempt at summarizing the present research in the life and career of Oribasius. The authors are in favour of the view that Oribasius was a native of Pergamum in Asia Minor. He was born in a well-off, most probably pagan, family and appears to have been first educated in the city of his birth. The cultural tradition of Pergamum and especially its renown as a centre of medicine must have had a considerable influence upon his future profession. Having completed the first stage of education, the young men left Asia Minor for Alexandria, which at that time still was the most important centre of medical science. There he studied under Zeno of Cyprus, a famous iatrosophist of that time. In the year 355 he had been already a good acquaintance of the future emperor Julian and after the latter’s elevation to the position of caesar, Oribasius accompanied Julian to Gaul, where he was one of the closest friends of that member of the imperial family. We know that he was in charge of Julian’s library and presumably took care of the caesar’s health. The doctor’s political influence is hard to precise but Oribasius is alleged to have played an undefined but important role in Julian’s usurpation. Later on he accompanied the rebel on his campaign against the legitimate ruler. When Julian took over the rule over the empire, Oribasius was also at his side. Some sources claim that he was even made quaestor at Constantinople. Subsequently, he left the capital, moved with the young emperor to Antioch and followed the ruler on his campaign against Persia. When Julian was fatally wounded, first he tried to save his life and then was present at the young ruler’s death-bed. Some time after Julian’s demise, he was exiled from the empire. He stayed for an unspecified time among the barbarians, managing to win their favour due to his competence in the area of medicine. He was called back by emperor Valens or Theodosius and allowed to settle down in Constantinople. Later on his property was also restored to him. Eunapius of Sardes, his biographer, informs us that he married a rich Constantinopolitan lady and fathered four children. He passed away at the very end of the IV th or at the beginning of the next century. Though little can be said about new theories or methods introduced by Oribasius in the area of medical science, the doctor earned his name as one of the most appreciated medical writers of Antiquity and Byzantium. He was prolific enough to write a voluminous work in seventy books, another one in nine books dedicated to his son Eustathius, a medical encyclopaedia in four books for his biographer Eunapius and a shorter treatise which is no longer extant. Additionally, he authored memoires describing important political developments he participated in. The extant medical works prove Oribasius’ considerable learning, display very clear organization and practicality, i.e. the features which contributed to the popularity of the doctor’s writings in late Antiquity, Byzantium as well as later on.